2022
DOI: 10.1016/j.porgcoat.2021.106632
|View full text |Cite
|
Sign up to set email alerts
|

Potential of engineered nanostructured biopolymer based coatings for perishable fruits with Coronavirus safety perspectives

Abstract: Fresh fruits are prioritized needs in order to fulfill the required health benefits for human beings. However, some essential fruits are highly perishable with very short shelf-life during storage because of microbial growth and infections. Thus improvement of fruits shelf-life is a serious concern for their proper utlization without generation of huge amount of fruit-waste. Among various methods employed in extension of fruits shelf-life, design and fabrication of edible nanocoatings with antimicrobial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…COVID-19 incidences resulted in millions of infections and deaths worldwide because of its fast spreadability. Like the drugs, healthy fruits with excellent nutritional value have been promoted during the COVID-19 crisis [ 107 ]. While the pandemic significantly impacted the economy, it also significantly influenced the healthy supply chain in the forms of fruits from farm to plate due to labor shortages, transportation limitations, and outdoor activities.…”
Section: Biopolymers For Food Applicationsmentioning
confidence: 99%
“…COVID-19 incidences resulted in millions of infections and deaths worldwide because of its fast spreadability. Like the drugs, healthy fruits with excellent nutritional value have been promoted during the COVID-19 crisis [ 107 ]. While the pandemic significantly impacted the economy, it also significantly influenced the healthy supply chain in the forms of fruits from farm to plate due to labor shortages, transportation limitations, and outdoor activities.…”
Section: Biopolymers For Food Applicationsmentioning
confidence: 99%
“…Thus, it is highly recommended to use hand sanitizers to prevent virus infection. However, it is challenging to wash some foods, such as strawberries and crinkly lettuce [66] , [67] , [68] , [69] , [70] . Environmentally friendly edible films and coatings are becoming increasingly important for human safety and fruit shelf life.…”
Section: Resultsmentioning
confidence: 99%
“…Environmentally friendly edible films and coatings are becoming increasingly important for human safety and fruit shelf life. By coating berries with edible antiviral coatings made of alginate/oleic acid and green tea extract, Falco et al (2019) demonstrated the control of viral infection and increase in berry safety [64] , [65] , [66] , [67] , [68] . Particularly, they found that the coatings exhibited high antibacterial activity against foodborne viruses, murine norovirus, and human norovirus.…”
Section: Resultsmentioning
confidence: 99%
“…This property can be useful in the design of active food packaging material since they can assist in ensuring heat balance within the film's microsphere, that may otherwise cause food product deterioration. Available literature has shown that perishable food products such as the locust beans typically produce oxygen, hydrogen, nitrogen, water vapor, carbon dioxide or methane during packaging (Kim et al 2014;Ghosh and Singh 2022;Zhao et al 2022). This can lead to a structural imbalance that can impact shelf life.…”
Section: Discussionmentioning
confidence: 99%